INTERPRETIVE ETHNOACCOUNTING: UNDERSTANDING ETHNOGRAPHYIN THE ACCOUNTING RESEARCH FIELDS - Sukoharsono, Eko Ganis (Accounting Department,, 2014)
The purpose of the paper is to explore a practical model of ethnography research method for ethnoaccountingsocial and culture. Ethnography is a aninterpretive account of what is lived and understood of a cultureof accounting phenomena. This culture is itself a contextual process that is ongoing, elusive and constantly modified.Ethnoaccounting is a terms used to elucidate where accounting phenomena contextually engaged in society and/ or organization. Â Clear steps are introduced where an accounting researcher interested to become an accounting ethnographer. The steps are ranging from understanding the history of ethnography, variety ethnographies, and Preparing for ethnography, to interpretation and reflexivity. Two ethnoaccounting research are described to elucidate the use of ethnography in accounting fields which are Nestleâ€™s creative shared value and the history of accounting practices in the era of the King of Udayana. In an essence, ethnography could provide a mode of social and cultural interpretations hidden in the accounting fields.